2015
DOI: 10.1007/s12182-015-0049-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of shale imbibition capacity and the factors influencing loss of hydraulic fracturing fluids

Abstract: Spontaneous imbibition of water-based fracturing fluids into the shale matrix is considered to be the main mechanism responsible for the high volume of water loss during the flowback period. Understanding the matrix imbibition capacity and rate helps to determine the fracturing fluid volume, optimize the flowback design, and to analyze the influences on the production of shale gas. Imbibition experiments were conducted on shale samples from the Sichuan Basin, and some tight sandstone samples from the Ordos Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 14 publications
6
67
0
Order By: Relevance
“…The process of water absorption by the clay minerals in the shale is referred in short as clay hydration. Several authors (Makhanov et al 2014;Ge et al 2015;Yang et al 2016) have reported that imbibed volume in some samples can be greater than the initially measured pore volume, which they suggested was due to absorption of water molecules by the semi-permeable clay membranes. Yang et al (2016) reported that this imbibed volume can be up to 400% of the pore volume measured before imbibition.…”
Section: Clay Hydrationmentioning
confidence: 91%
“…The process of water absorption by the clay minerals in the shale is referred in short as clay hydration. Several authors (Makhanov et al 2014;Ge et al 2015;Yang et al 2016) have reported that imbibed volume in some samples can be greater than the initially measured pore volume, which they suggested was due to absorption of water molecules by the semi-permeable clay membranes. Yang et al (2016) reported that this imbibed volume can be up to 400% of the pore volume measured before imbibition.…”
Section: Clay Hydrationmentioning
confidence: 91%
“…Here, we model the capillary imbibition phase in a shale sample and compare the results with the experimentally measured data points. Although the characteristics of water imbibition curves in different tight rocks vary significantly (attributed to different matrix and pore space structures), generally, the imbibition curve is divided into the following three regions: (1) initial linear capillary imbibition (which is the focus of this work); (2) transition region, which occurs at higher water saturations where the role of capillary driving force gradually diminishes; and (3) diffusion region, which occurs in longer periods . Roychaudhuri et al considered spontaneous water imbibition into cubic samples of 1 cm 3 taken from the Marcellus shale member of the Appalachian Basin to investigate the role of capillary imbibition in the fracking fluid intake process.…”
Section: Workflow Of Semi‐analytical Modellingmentioning
confidence: 99%
“…During shut‐in periods, the pressure gradient (viscous force) gradually diminishes and the capillary force takes over the water intake via a slow countercurrent imbibition process . Recent core‐scale observations confirm that the capillary imbibition plays a remarkable role in fluid migration from fracture to matrix and is mainly controlled by the rock and fluid properties, fracture interface, and shut‐in‐time length …”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous imbibition refers to the process of adsorption with no pressure driving of the phases into the rock. Some experimental investigations were also performed on shale imbibition capacity towards hydraulic fracturing fluids [10,11]. Currently, it is well known that the imbibition of fracturing fluids is mainly controlled by the capillary pressure, while the effects of clay absorption have not been studied thoroughly [10].…”
Section: Fluid Absorption In Shalementioning
confidence: 99%
“…Some experimental investigations were also performed on shale imbibition capacity towards hydraulic fracturing fluids [10,11]. Currently, it is well known that the imbibition of fracturing fluids is mainly controlled by the capillary pressure, while the effects of clay absorption have not been studied thoroughly [10]. Because different mechanisms seem to be facilitating imbibition in the shale, there is not so far a verified answer for the geomechanisms behind those observations [11].…”
Section: Fluid Absorption In Shalementioning
confidence: 99%